Help-seeking and needs of male victims of intimate partner violence in portugal - Machado, Andreia Patrícia Guimarães (2016)
A large body of research clearly indicates that men are victims of intimate partner violence (IPV). However, in Portugal, the phenomenon of male victims of IPV remains hidden and is not a target of research, public policy, or social attention. This exploratory study analyzed the prevalence of victimization, help-seeking behaviors, and needs of 89 men who defined themselves as victims of IPV. Men reported that they had been the victims of at least 1 abusive behavior by their current or former female partner. Psychological violence, followed by physical and sexual violence, was the most frequently reported experience. The majority of the men did not seek help because of difficulty in self-identifying as victims, shame, and distrust of the support system. When they did seek help, informal sources, such as friends and family, were used more often than formal sources. In terms of formal support, victims used health professionals and social/victim support services more than any other type. The male victims evaluated the formal resources (e.g., social/victim support services, police, justice system) as unhelpful. A mediation model showed that both frequency of physical violence and self-reported impact of IPV predicted help-seeking, with impact of IPV partially mediating the association between physical IPV and help-seeking. The results indicate the difficulties that men have in recognizing themselves as victims of abuse, their reluctance to seek help, the barriers they face, and their heterogeneous and idiosyncratic needs. The implications regarding masculinity, the help-seeking system, and public policy are discussed.